2007
DOI: 10.1097/shk.0b013e31812386bf
|View full text |Cite
|
Sign up to set email alerts
|

ENDOTOXIN IMPAIRS THE HUMAN PACEMAKER CURRENT I f

Abstract: all 10 cities including the rural areas of the province of Kerman. All data were finally analyzed by SPSS software (version 11.5). Results On the basis of recorded statistical analysis, the mortality cases of human rabies in the province of Kerman during one decade was 10 persons (eight males and two females). One-half of them (50%) were bitten by dogs and the others (50%) by foxes. Among the reported deaths, 40% were from Kahnooj county (Jiroft region). The reported data indicated that 21,546 persons were bit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 37 publications
3
41
0
1
Order By: Relevance
“…[48][49][50] One explanation of the development of new onset atrial fibrillation events in sepsis is the imbalance between sympathetic and vagal tone in sepsis leading to a reduction of heart rate variability (HRV) [3,51]. In a study on human atrial cardiomyocytes, Zorn-Pauly et al [26] identified a gram-negative bacteria -endotoxin-induced I(f) impairment, which might contribute to a reduced responsiveness to both sympathetic and vagal autonomic stimuli. It might be argued that decreased responsiveness to autonomic stimuli would affect HRV [52].…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…[48][49][50] One explanation of the development of new onset atrial fibrillation events in sepsis is the imbalance between sympathetic and vagal tone in sepsis leading to a reduction of heart rate variability (HRV) [3,51]. In a study on human atrial cardiomyocytes, Zorn-Pauly et al [26] identified a gram-negative bacteria -endotoxin-induced I(f) impairment, which might contribute to a reduced responsiveness to both sympathetic and vagal autonomic stimuli. It might be argued that decreased responsiveness to autonomic stimuli would affect HRV [52].…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…These arrhythmias may be explained by autonomic dysfunction or impairment and involvement of the cardiac conduction system rather than to pre-existing cardiac co-morbidities [26,27]. This paper will focus on clinical features of arrhythmias and potential pathophysiologic mechanisms of the cardiac conduction system disturbances in septic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on telemetry studies in mice, this reduction in HRV is attributable to lipopolysaccharide (LPS; Ref. 5); however, it remains uncertain whether this action of LPS results from its direct effect on heart cells (41,47) or broader effects involving the central and autonomic nervous systems (6).…”
mentioning
confidence: 99%
“…Dass diese Beein trächtigung der Herzfrequenzregulation nicht ausschließlich auf indirekten, durch Mediatoren des Immunsystems vermit telte Mechanismen beruht, sondern zu mindest teilweise auf eine direkte Inter aktion von Endotoxin mit Sinusknoten zellen zurückzuführen ist, konnten wir zwischenzeitlich anhand von Zellkultur versuchen nachweisen: Elektrophysiolo gische Untersuchungen an isolierten hu manen Vorhofmuskelzellen konnten bele gen, dass Endotoxin zum einen direkt den Schrittmacherstrom ("funny current", If) durch Beeinflussung der verantwortlichen HCNKanäle ("hyperpolarizationactiva ted cyclic nucleotidegated cation chan nel") zu hemmen vermag und anderer seits diese Kanäle gegenüber der Sympa thikusbeeinflussung empfindlicher macht -in einem mathematischen Modell kön nen diese Beobachtungen etwa 50% der HRVStarre erklären [27].…”
Section: Introductionunclassified